Yeast population dynamics during prefermentative cold soak of Cabernet Sauvignon and Malbec wines - Maturano, Yolanda Paola; Mestre Furlani, Maria Victoria; Esteve Zarzoso, Braulio; Nally, María Cristina; Lerena, María Cecilia; Toro, Maria Eugenia; Vazquez, Fabio; Combina, Mariana (2018)
Prefermentative cold soak is a widely used technique in red wine production, but the impact on the development of native yeast species is hardly described. The aim of this work was to analyse the dynamics and diversity of yeast populations during prefermentative cold soak in red wines. Three different temperatures (14 ± 1 °C; 8 ± 1 °C and 2.5 ± 1 °C) were used for prefermentative cold soak in Cabernet Sauvignon and Malbec grape musts. Saccharomyces and non-Saccharomyces populations during cold soak and alcoholic fermentation were analysed. In addition, the impact on chemical and sensory properties of the wines was examined. Yeast dynamics during prefermentative cold soak were temperature dependent. At 14 ± 1 °C, the total yeast population progressively increased throughout the cold soak period. Conversely, at 2.5 ± 1 °C, the yeast populations maintained stable during the same period. Prefermentative cold soak conducted at 14 ± 1 °C favoured development of Hanseniospora uvarum and Candida zemplinina, whereas cold soak conducted at 8 ± 1 °C favoured growth of Saccharomyces cerevisiae. At 2.5 ± 1 °C, no changes in yeast species were recorded. Acidity and bitterness, two sensory descriptors, appear to be related to wines produced with prefermentative cold soak carried out at 14 ± 1 °C. This fact could be associated with the increase in non-Saccharomyces during the prefermentation stage. Our results emphasise the importance of the temperature as a determinant factor to allow an increase in non-Saccharomyces population during prefermentative cold soak and consequently to modify sensorial attributes of wines as well as their sensorial impact.